Global Muckraking: The International Impact Of Upton Sinclair's The Jungle - Hussey, Michael (Teaching History: A Journal of Methods, 2009)
On October 9, 1907, Robert Bacon, Acting Secretary of State, wrote to the United States ambassador in London, Whitelaw Reid, that satirical postcards regarding the U.S. meat industry were circulating in South Africa. Originally published in England, these cards depict the plight of a rooming house lodger attempting to eat various samples of "Chicago tinned meat." In one scene, a scrawny fowl emerging from a can of potted chicken cries out, "Was anyone asking for me?" In another, the unfortunate lodger turns away and holds his nose as a can of "awful, rotten, [and] putrid" ham and tongue is opened. R.L. Graycroft, Cape Town general manager of the meatpacking firm Armour and Company, complained to the U.S. consul in that city that the postcards were libelous to "Chicago and damaging to our business." British colonial authorities had rejected Graycroft's allegation of libel since the cards never mentioned a particular meatpacking firm.